Выражение (3√2-1)(1+3√√2-√1,5)^2-6√2.8класс

margaritrw margaritrw    3   16.08.2019 05:00    1

Ответы
Set1z1337 Set1z1337  04.10.2020 22:19
(3√2-1)(3√2+1)-(3√2-√1,5)²-6√3=18-1-18+6√3-1,5-6√3=-2,5
ПОКАЗАТЬ ОТВЕТЫ
dilyara112005 dilyara112005  04.10.2020 22:19
(3√2  - 1)(1+3√2) - (3√2 - √1,5)^2 - 6√2=(3√2)^2 - 1 -((3√2)^2 - 2·3√2·√1,5 + (√1,5)^2) - 6√2 = 9·2 - 1 - 9·2 +6√3 -1,5 - 6√2= 6√3-6√2-2,5
 {можно также вынести общий множитель:}
=6 (√3-√2) - 2,5
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра